Hubungan Ergonomi dan Durasi Kerja Terhadap Kejadian Myofascial Pain Syndrome pada Pekerja Kantoran - Yvone Sarah; Annisa Tri Andriani; Febri Endra Budi Setyawan (ARTERI : Jurnal Ilmu Kesehatan, 2023)
The use of computers in office workers often creates health problems related to musculoskeletal disorders or MSDs. WHO noted that until 2021, there are about 1.71 billion people with musculoskeletal disorders. The result of using computers in office workers exceeds the specified time limit and posture while working is not appropriate and occurs repeatedly and continuously causes myofascial pain syndrome (MPS) in the upper trapezius, part of the neck. MPS can cause discomfort to workers, work-related accidents increase, worker performance decreases, resulting in increased worker absenteeism. This literature review aims to determine the relationship between ergonomics and work duration on the incidence of Myofascial Pain Syndrome in office workers. The method used is a qualitative literature study. The conclusion from this literature review is that the application of poor ergonomics and prolonged working hours (the ILO recommended 8 hours a day) will affect the MPS.